2019
DOI: 10.1016/j.neuron.2019.01.012
|View full text |Cite
|
Sign up to set email alerts
|

A Mast-Cell-Specific Receptor Mediates Neurogenic Inflammation and Pain

Abstract: Highlights d The mast cell receptor Mrgprb2 is required for neurogenic inflammatory pain d Substance P (SP) recruits immune cells via Mrgprb2 independent of the NK-1 receptor d SP activation of Mrgprb2 and its human ortholog MRGPRX2 releases cytokines d Mrgprb2/X2 is a target for treating pain SUMMARYMast cells can be found in close proximity to peripheral nerve endings where, upon activation, they release a broad range of pro-inflammatory cytokines and chemokines. However, the precise mechanism underlying thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
248
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(256 citation statements)
references
References 32 publications
(30 reference statements)
6
248
2
Order By: Relevance
“…The receptors for other neuropeptides, Tac1, Adcyap1, and Gal (Tacr1, Adcyap1r1, and Galr2 & Galr1, respectively) were uniquely expressed by NES, identifying substance P, 20 PACAP, and galanin as potential signaling mediators between LN-innervating neurons and NES. Notably, the recently identified alternative substance P receptor Mrgprb2 was almost exclusively expressed at high level in LN mast cells, suggesting a substance P/Mrgprb2 mediated sensory neuron-mast cell connection analogous to what 510 was described in the skin (Green et al, 2019). By contrast, classic neuropeptides were not a primary mode of communication between LN-innervating sensory neurons and LN endothelial cells.…”
Section: S5o See Methods)mentioning
confidence: 68%
“…The receptors for other neuropeptides, Tac1, Adcyap1, and Gal (Tacr1, Adcyap1r1, and Galr2 & Galr1, respectively) were uniquely expressed by NES, identifying substance P, 20 PACAP, and galanin as potential signaling mediators between LN-innervating neurons and NES. Notably, the recently identified alternative substance P receptor Mrgprb2 was almost exclusively expressed at high level in LN mast cells, suggesting a substance P/Mrgprb2 mediated sensory neuron-mast cell connection analogous to what 510 was described in the skin (Green et al, 2019). By contrast, classic neuropeptides were not a primary mode of communication between LN-innervating sensory neurons and LN endothelial cells.…”
Section: S5o See Methods)mentioning
confidence: 68%
“…As well known, mast cells mediate neurogenic inflammation and pain [28]. The activated and degranulating mast cells may exert indirect effects on the development of neuropathic pain [29].…”
Section: Mifepristone Inhibits the Infiltration And Activity Of Degramentioning
confidence: 99%
“…SP also modulated the immune response to microbial infection (29). It was recently demonstrated that SP could promote the migration and activation of mast cells, inducing the release of multiple pro-inflammatory cytokines and chemokines (30). Noteworthy, SP directly caused the secretion of IL-8 in human colonic epithelial cell lines (31), hinting at the potential proinflammatory role of SP in intestine.…”
Section: Trp Channels In the Gi Tract And Related Neuropeptidesmentioning
confidence: 99%